Anxiety disorders in Malaysia from 2005 to 2015: a scoping review of their prevalence rates, associated factors, and predictors - Abdul Khaiyom, Jamilah Hanum; Mukhtar, Firdaus; Oei, Tian Po Sumantri (Faculty of Medicine, Universiti Malaya, 2021)
Introduction: The current study aims to investigate the prevalence rates, associated factors, and predictors of anxiety disorders in Malaysia through a scoping review.